Avocado Rootstock Propagation Techniques to Support The Readiness of Ngesrepbalong Village, Limbangan Kendal as An Avocado Center - Retnoningsih, Amin; Rahayu, Enni Suwarsi; Mustofa , Moh. Solehatul; Akbar, Bintang Faisal; Karmesti, Danissa Wirna (Universitas Negeri Semarang, 2025)
Ngesrepbalong Village in Limbangan District, Kendal, is known to be prone to landslides. Landslide mitigation through planting deep-rooted trees. This village was classified as a developing village until the end of 2023. Efforts to realize Ngesrepbalong as an avocado center required intensifying superior avocado cultivation, which involved mass availability of seeds. The problem was that the rootstock in avocado grafting was limited because one avocado only produced one seed. The production problems of the target partners of